EDM : the educator's diagnostic manual of disabilities and disorders - Pierangelo, Roger; Giuliani, George (San Francisco, California : Jossey-Bass Inc., Publishers, 2007)
The definitive resource for special educators, school psychologists, and child group study teams This comprehensive guide provides all the information needed -- including definitions, symptoms, characteristics, and types -- for the most significant educational disabilities and disorders, presented in a user-friendly format. Using the reauthorized IDEA 2004 Act as a frame of reference, this book is ideal for coding and mapping to IEPs -- the individualized education plans that are key to special education funding. The very first manual created specifically for education professionals, this book addresses a range of disorders and relates their significance to classroom practice, including: Autism Spectrum Disorder, Developmental Delays, Mental Retardation, Traumatic Brain Injury, and many others.
1. Special learning disability -- 2. Speech and language impairments -- 3. Mental retardation -- 4. Emotional disturbance -- 5. Other health impairments -- 6. Multiple disabilities -- 7. Autism -- 8.Orthopedic impairments -- 9. Hearing impairments -- 10. Visual impairments -- 11. Traumatic brain injury -- 12. Deaf-blindness -- 13. Infants, toddlers and preschoolers with disabilities -- 14. Using the EDM in IEP development.
Includes bibliographical references and index.
Keywords: CHILDREN WITH DISABILITIES -- IDENTIFICATION